Analysis Of Added Value Of Arabica Coffee Processing At PT. Dete kopi Kintamani, Bali - Sijabat, John Howard; I Wayan Gede Sedana Yoga; Lutfi Suhendra (International Journal of Economics, Business and Innovation Research, 2026)
Coffee processing plays a crucial role in generating added value, significantly contributing to producers’ income. This study analyses the value added from processing Arabica red cherry coffee into green beans using three methods: Full Wash, Honey Process, and Natural Process. at PT. Dete Kopi in Kintamani, Bali. The Hayami method was employed to quantify the added value based on output conversion, input cost, and profitability. Data were collected through interviews, field observations, and document analysis. The results revealed that the Natural Process yielded the highest added value, amounting to IDR 11,846 per kilogram (40.85%), followed by the Honey Process at IDR 8,673/kg (33.36%), and Full Wash at IDR 8,556/kg (32.91%). Key factors influencing value creation included raw material quality, weather conditions, availability of drying space, labor, production costs, capacity, and processing techniques. This study underscores the